The breast cancer oncogene IKKε coordinates mitochondrial function and serine metabolism. (11th August 2020) - Xu, Ruoyan; Jones, William; Wilcz‐Villega, Ewa; Costa, Ana SH; Rajeeve, Vinothini; Bentham, Robert B; Bryson, Kevin; Nagano, Ai; Yaman, Busra; Olendo Barasa, Sheila; Wang, Yewei; Chelala, Claude; et al.
Abstract: IκB kinase ε (IKKε) is a key molecule at the crossroads of inflammation and cancer. Known to regulate cytokine secretion via NFκB and IRF3, the kinase is also a breast cancer oncogene, overexpressed in a variety of tumours. However, to what extent IKKε remodels cellular metabolism is currently unknown. Here, we used metabolic tracer analysis to show that IKKε orchestrates a complex metabolic reprogramming that affects mitochondrial metabolism and consequently serine biosynthesis independently of its canonical signalling role. We found that IKKε upregulates the serine biosynthesis pathway (SBP) indirectly, by limiting glucose‐derived pyruvate utilisation in the TCA cycle, inhibiting oxidative phosphorylation. Inhibition of mitochondrial function induces activating transcription factor 4 (ATF4), which in turn drives upregulation of the expression of SBP genes. Importantly, pharmacological reversal of the IKKε‐induced metabolic phenotype reduces proliferation of breast cancer cells. Finally, we show that in a highly proliferative set of ER negative, basal breast tumours, IKKε and PSAT1 are both overexpressed, corroborating the link between IKKε and the SBP in the clinical context. Synopsis: The IκB kinase IKKε inhibits mitochondrial metabolism by limiting pyruvate oxidation, in turn activating the serine biosynthesis pathway via ATF4 in a NFκB and IRF3‐independent manner. IKKε limits pyruvate oxidation via indirect modulation of the pyruvate dehydrogenase complex. Inhibition of mitochondrial metabolism induces the activation of ATF4 and consequently the upregulation of PSAT1. IKKε and PSAT1 are both overexpressed in a set of highly proliferative ER‐basal breast cancer tumours. Abstract : The IκB kinase IKKε inhibits mitochondrial metabolism by limiting pyruvate oxidation, in turn activating the serine biosynthesis pathway via ATF4 in a NFκB and IRF3‐independent manner.